As condiÃÃes de acesso e permanÃncia dos estudantes do Curso de Licenciatura em FÃsica do IFCE, Campus de Sobral - NÃrlia Nabuco Parente (2014)
This study aims to analyze the conditions of access and permanency of students in the under-graduate program in Physics at the Instituto Federal de EducaÃÃo, CiÃncia e Tecnologia do CearÃ (IFCE), Sobral campus. Its relevance is justified on the numbers of evasion of the course, that even with the actions developed under the student assistance, remain troubling. The argument contextualizes the expansion of higher education and the role of the federal technologic network, addressing the access and permanency politics, in the light of Bourdieu's theoretical perspective. This is a case study with quantitative and qualitative analysis. The methodological approach follows the steps: gathering information from Sisu and knowledge of ENEM for socioeconomic and cognitive profile of the student; analysis of the transcripts, noting yields and correlations; use of interviews and questionnaires the subjects for collecting their perceptions; thematic synthesis of results obtained from the SWOT analysis model, us-ing strengths, weaknesses, threats and opportunities, from the aspect of permanence. The sample unit consisted of 17 freshmen at 2013.1, as well as professors and course coordinator in this period. The correlation coefficient was calculated Person to examine the degree of as-sociation between performance in the examination and in introductory courses. The infor-mation collected in interviews and questionnaires went through the content analysis from the perspective of Bardin, to visualize nuclei organizers of discourses, categories, conflicts and consensus. Regarding the profile and conditions of access, the survey results showed that: students are male; they reside outside of Sobral; they come from families with family income less than 1.5 times the minimum wage and little education; they joined the waiting list with an average of 580.56 points in ENEM. As for permanence, it was found that: More than half of these freshmen have dropped out of the course, even if the institution has a politic of assis-tance and the course has scholarships and research projects and extension. As for perfor-mance, it was found that there are many failures in the first half, especially in Basic Mathe-matics, with a strong correlation between score in ENEM and performance in the introductory courses. Regarding perceptions of the subjects, those who recognize the factors that contribute to the permanence and performance are: bibliographic; scholarships and research projects / extension; infrastructure; interaction with peers and teachers; quality of teaching. Factors that hinder are episodes of strike; lack of teachers, laboratories and academic restaurant; financial difficulties in reconciling work and study and transportation.